Analisis Perbandingan Kinerja dan Kegunaan Aplikasi Pengelola Kata Sandi Closed-Source berdasarkan ISO/IEC 25010 - Whisnu Yudha Aditama; Ira Rosianal Hikmah (Universitas Hamzanwadi, 2022)
The number of services used by internet users such as social media, online transportation, entertainment, and banking. this encourages the use of weak, short, and repetitive passwords that can trigger sensitive data leaks and impact individuals or organizations. These problems can be overcome with open-source and closed-source password manager applications to help users create, store, and manage passwords. Closed-source password manager apps have an advantage in the features they provide compared to open-source ones. The many providers of password manager applications make users face many choices so that the specifications of the password manager application need to be known as consideration for determining the application to be used. In this study, a comparative analysis was conducted to assess the advantages and disadvantages of several popular and widely used closed-source password management applications, including Lastpass, 1Password, and Keeper. Comparative analysis was carried out based on the performance, and usability of ISO/IEC 25010. This study used mixed methods. Quantitative data was obtained during performance testing, while qualitative data was obtained when distributing questionnaires to measure usability. The result is that, in terms of performance characteristics, each application has its own advantages in a different sub-characteristic. On usability characteristics, Keeper application excels in four sub characteristics while 1Password excels in two sub characteristics.